Hybrid Bees Algorithm to Solve Aircraft Landing Problem - Abdul-Razaq, T. S.; Ali, F H. (Sulaimani Journal for Pure and Applied Sciences, 2015)
In this paper, we study the aircraft landing problem (ALP), which considered as one of a combinatorial optimization problems, in a single runway case. We present in the first part, a mathematical formulation of the problem with a linear objective function. In the second part, we consider the static case of the problem where all data are known in advance. We present a new heuristic for scheduling static case of aircraft landing; this heuristic is incorporated into Bees algorithm to solve this problem.
Keywords: Aircraft Landing Problem; Swarm Intelligence; Bees Algorithm